CHARACTER BUILDING ON YOUNG PEOPLE: INVESTMENT TO BE A TOUGH LEADER - Arundati Shinta, Dewi H. Harahap & Eny Rohyati (Jurnal Psikologi, 2014)
Process of building character on young people started from the habit changing and the provision of activity meaning. The habit changing was applied through conducting ordinary activities among young people i.e. sport / physical recreation, skill training, community service and adventure / expedition. Those 3 former activities should be conducted continuously at least 6 months, during 60 minutes / activity / week, whilst the adventure / expedition should be conducted at least 2 days till 14 days, based on the character changing level (bronze, silver, and gold). Those activities were under the IAYP (International Award for Young People) program. The provision of activity meaning was the participant's interpretation whether these activities were burden or challenge. When the burden interpretation occurred, participant would be likely to tell a lie, lazy, broken his or her commitment to accomplish the activities, and try to find creative apology to cover the laziness. When the challenging interpretation occurred, participant would be likely to have good characters i.e. tough, internal self-regulation, honest, interpreting disability as opportunity, high commitment, and patient. This character building on young people is a precious investment to be a though leader.Method of this research was monitoring student's self report on accomplishing those 4 activities under the IAYP program. Monitoring meant reminding (motivating) participant toward his or her commitment, instructing participant to repeat those activities from the initial start when he or she was lazy, and reminding participant to choose middle risk adventure activity instead of high or low risk activity. There were 13 participants (6 girls, 7 boys), university students, mean age was 20. All of them wanted to achieve the bronze award. Those students participated to the IAYP individually; therefore their completion time was dissimilar. By the end of research (month 11), 4 students succeeded in achieving bronze award. One participant was drop out because had other commitment, whilst the rests (8 students) were still in progress. Two of those 8 students should repeat again their activities from the initial start, since they broke their schedule commitment.